Tinjauan Siyasah Maliyah terhadap Regulasi Pengelolaan Zakat di Lembaga Amil Zakat Rumah Zakat Kota Bandung berdasarkan Undang-Undang No.23 Tahun 2011 - Abiyyu Mufid Jadid Pasya; Idzam Fautanu; Lutfi Fahrul Rizal (Jurnal Hukum Lex Generalis, 2025)
Public financial policy broadly regulates the income, management, and expenditures of state finances while considering the welfare of society. One source of funding in Sharia is zakat. In its implementation, the state plays a role in optimally managing zakat funds, in Indonesia, the provisions concerning zakat are regulated under Law No. 23 of 2011 on the Management of Zakat, where BAZNAS becomes a semi-autonomous body directly responsible to the president. The presence of BAZNAS serves as both a regulator and an operator that collects zakat funds, which has led to various viewpoints in Indonesia. Ultimately, the Zakat Management Institutions (LAZ) that are part of the Zakat Forum (FOZ) conducted a judicial review at the Constitutional Court to obtain legal certainty.